2018
DOI: 10.1596/1813-9450-8525
|View full text |Cite
|
Sign up to set email alerts
|

Should I Stay or Should I Go: Do Cash Transfers Affect Migration?

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 26 publications
2
16
0
1
Order By: Relevance
“…However, as shown byAdhikari and Gentilini (2018), if not properly designed, unrestricted cash transfers to poor people can have the opposite effect and, by alleviating income constraints, can actually increase emigration from low income countries. This is consistent with this study's finding showing that low income is one of the main barrier preventing youth from turning migration desire into more concrete plans.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, as shown byAdhikari and Gentilini (2018), if not properly designed, unrestricted cash transfers to poor people can have the opposite effect and, by alleviating income constraints, can actually increase emigration from low income countries. This is consistent with this study's finding showing that low income is one of the main barrier preventing youth from turning migration desire into more concrete plans.…”
mentioning
confidence: 99%
“…More generally, most of developing and emerging countries are undergoing significant transformations, including greater integration in global value chains, increasing employment in services, intensifying urbanization, and growing enrolment rates in post-secondary education. Managing these processes, focusing on the equitable generation and distribution of education and decent job opportunities for youth in both rural and urban areas, may ultimately have important implications on international migration flows(Adhikari and Gentilini, 2018).…”
mentioning
confidence: 99%
“…on this e.g. Gesellschaft für Versicherungswissenschaft und -gestaltung (2017); Adhikari and Gentilini (2018). 92 See also Martens and Vandenhole, in this volume.…”
Section: Resultsunclassified
“…The growing number of cash transfer programs in low-and middle-income countries could relax some of these constraints and further fuel international migration. Yet, empirical evidence on the link between cash transfers and international migration is limited (Adhikari and Gentilini, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Our paper makes an important contribution to the literature on the effects of cashbased programming on international migration. In a recent review, Adhikari and Gentilini (2018) identified only three empirical studies exploring the effects of cash transfer programs on international migration, all of which focus on the Mexico-US migration. Both Stecklov et al (2005) and Angelucci (2015) exploit random variation in the rollout of the Progresa program of conditional cash transfer, but while Stecklov et al (2005) find that Progresa reduced overall migration to the US, Angelucci (2015) finds that Progresa increased labor migration to the US.…”
Section: Introductionmentioning
confidence: 99%